New Medications for Substance Use Disorders: Challenges and Opportunities - Volkow, Nora D (Nature Publishing Group, 2012)
An increased understanding of the biological mechanisms underlying the process of addiction has led to unique molecular targets and strategies for pharmacotherapies against addiction. However, the successful translation of these discoveries will require: 1) a more active engagement of the pharmaceutical sector, 2) partnership with regulatory agencies to arrive at meaningful outcomes for medication approval and 3) a greater involvement of the healthcare system in the screening and treatment of substance use disorders.